2008
DOI: 10.4103/0019-5413.43398
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure from fluoroscopy during fixation of hip fracture and fracture of ankle: Effect of surgical experience

Abstract: Background:Over the years, there has been a tremendous increase in the use of fluoroscopy in orthopaedics. The risk of contracting cancer is significantly higher for an orthopedic surgeon. Hip and spine surgeries account for 99% of the total radiation dose. The amount of radiation to patients and operating surgeon depends on the position of the patient and the type of protection used during the surgery. A retrospective study to assess the influence of the radiation exposure of the operating surgeon during fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
(14 reference statements)
2
29
0
1
Order By: Relevance
“…This showed that the experience of the operating surgeon is an independent factor for determining radiation exposure to patients for hip fracture fixation. 3 Fluoroscopy use has increased in the field of orthopaedics, and there is also a consideration for the effects of radiation exposure to the surgeon and operating theatre staff. However, this has been discussed in other studies and is not mentioned here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the experience of the operating surgeon is an independent factor for determining radiation exposure to patients for hip fracture fixation. 3 Fluoroscopy use has increased in the field of orthopaedics, and there is also a consideration for the effects of radiation exposure to the surgeon and operating theatre staff. However, this has been discussed in other studies and is not mentioned here.…”
mentioning
confidence: 99%
“…2 Radiation exposure during orthopaedic procedures using fluoroscopy is influenced by many factors including the type and difficulty of the procedure, patient position, radiation protection used and the experience of the surgeon. 3 Paediatric patients provide a unique challenge during surgery owing to their size. There is a risk for a severalfold increased radiation exposure due to the large size of the image intensifiers relative to the patient size.…”
mentioning
confidence: 99%
“…11,12 Botchu and Ravikumar analysed 60 patients with undisplaced intertrochanteric fractures and 60 with isolated lateral malleolar fractures without comminution who underwent fluoroscopically assisted fixation by the same approach and technique. 11 The authors broadly divided the hip and ankle groups depending on the operative experience of the operating surgeon (<3 years, 3-10 years and >10 years).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…11,12 Botchu and Ravikumar analysed 60 patients with undisplaced intertrochanteric fractures and 60 with isolated lateral malleolar fractures without comminution who underwent fluoroscopically assisted fixation by the same approach and technique. 11 The authors broadly divided the hip and ankle groups depending on the operative experience of the operating surgeon (<3 years, 3-10 years and >10 years). They concluded that the experience of the operating surgeon is one of the most important factors 2 SHO = senior house officer; SpR = specialist registrar Figure 1 For the lateral view, the C-arm should be positioned so that the femoral shaft, neck and head are in a straight line (bold lines).…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation